PELAKSANAAN FUNGSI BIROKRASI OLEH DINAS LINGKUNGAN HIDUP KABUPATEN KUANTAN SINGINGI DALAM PENGENDALIAN KERUSAKAN LINGKUNGAN AKIBAT AKTIVITAS PERTAMBANGAN EMAS TANPA IZIN (PETI) TAHUN 2020-2021 - Laura Aidilla Fitri; Adlin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Indonesia is a country rich in natural resources, one of which is mining. In Kuantan Singingi Regency mining is rife. There are mines in Kuantan Singingi Regency that have permits and some that do not have permits. But most of the mining in Kuantan Singingi Regency does not have official permits from the Regional Government. Which mining has a negative impact on environmental damage. Whereas in article 67 of Law 32 of 2009 concerning Environmental Protection and Management it is explained that "everyone is obliged to maintain environmental functions and control environmental pollution and/or damage". This study aims to determine the implementation of the bureaucratic functions of Kuantan Singingi Regency in controlling environmental damage due to Unlicensed Gold Mining (PETI) activities and to determine the factors causing the not maximal implementation of bureaucratic functions in controlling environmental damage due to Unlicensed Gold Mining (PETI). The method used in this research is a qualitative method with a descriptive research type. The results of this study are the implementation of the bureaucratic function of Kuantan Singingi Regency in controlling environmental damage due to Unlicensed Gold Mining (PETI) activities. To measure the components in the implementation of the bureaucratic functions of Kuantan Singingi Regency in controlling environmental damage due to Unlicensed Gold Mining (PETI) can be seen from the public service bureaucracy, development bureaucracy and service bureaucracy. And as for the factors causing the not maximal implementation of the bureaucratic function in controlling environmental damage due to gold mining activities without a permit, namely the lack of a budget, the absence of regional policies/regulations and the low level of community participation. Keywords: Public Service Bureaucracy, Development and Service